Effect of Reward and Punishment, Compensation, Leadership, and Workplace Skills on Employee Work Discipline at Mopah Class I Airport Management Unit - Kasmawati, Kasmawati; Sudarya, Agus; Zakaria, Zakaria (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study aimed to determine whether reward and punishment, compensation, leadership, and workplace skills affect employee work discipline. The sample of this study consisted of 108 respondents who were employees at Mopah Class I Airport Management Unit Office in Merauke. The independent variables in this study were reward and punishment, compensation, leadership, and workplace skills, while the dependent variable was employee work discipline. The data were collected by distributing questionnaires using a Likert scale. The data were analyzed using the multiple linear regression and IBM SPSS software. The results of the analysis showed that the variables of reward and punishment, compensation, leadership, and workplace skills had a positive and significant effect on work discipline.